#### Answer

(a) The spring exerts a force of 4.0 N on glider A.
(b) The spring exerts a force of 3.0 N on glider B.

#### Work Step by Step

We can find the acceleration of the system of glider A, the spring, and glider B. Let $M$ be the total mass of the system.
$F = Ma$
$a = \frac{F}{M}$
$a = \frac{6.0~N}{0.400~kg+0.200~kg+0.600~kg}$
$a = 5.0~m/s^2$
(a) Let's consider the system of glider A. We can use a force equation to find the force $F_{sA}$ that the spring exerts on glider A.
$\sum F = m_A~a$
$F-F_{sA} = m_A~a$
$F_{sA} = F-m_A~a$
$F_{sA} = (6.0~N)-(0.400~kg)(5.0~m/s^2)$
$F_{sA} = 4.0~N$
The spring exerts a force of 4.0 N on glider A.
(b) Let's consider the system of glider B. Note that the force $F_{sB}$ that the spring exerts on glider B provides the force to accelerate glider B.
$F_{sB} = m_B~a$
$F_{sB} = (0.600~kg)(5.0~m/s^2)$
$F_{sB} = 3.0~N$
The spring exerts a force of 3.0 N on glider B.